ARDUINO-BASED INTELLIGENT SYSTEM FOR EARLY DETECTION AND ALERTING SPOILAGE IN FOOD - P.Neelima, B.Madhavi, E.Ramesh Babu, B.Kishori; R.Usha (South Eastern European Journal of Public Health, 2025)
With the increasing dependence on smart approaches like mobile phones, there is a need for easy and rapid solutions to everyday problems in today's technological age. An Arduino-based food detecting system is the foundation of this project. A few of the things that the microcontroller panel can do include reading inputs and outputs and activating the sensor. The typical practice of storing food in a refrigerator reduces the pace of bacterial production. It is important to identify and notify the user of some things that are either easily spoilt or have a short shelf life. The main idea behind this project is to use sensors to detect when food is starting to spoil. The system will continuously sense signals from the food and display the pH value of methane on a 16*2 LCD panel. It will also include a buzzer and LED lights, and it will send an alarm message to the registered mobile phone. -Arduino, MQ4 Methane gas sensor, LCD display, Wi-Fi ESP 8266, alert message, LED—these are the keywords for this spoiled food detector.